Advances in Ergonomics in Design Proceedings of the AHFE 2018 International Conference on Ergonomics in Design, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Rebelo, Francisco; Soares, Marcelo M. (Advances in Intelligent Systems and Computing, 2019)
This book provides readers with a timely snapshot of ergonomics research and methods applied to the design, development and prototyping - as well as the evaluation, training and manufacturing - of products, systems and services. Combining theoretical contributions, case studies, and reports on technical interventions, it covers a wide range of topics in ergonomic design including: ecological design; educational and game design; cultural and ethical aspects in design; user research and human-computer interaction in design; as well as design for accessibility and extreme environments, and many others. The book particularly focuses on new technologies such as virtual reality, state-of-the-art methodologies in information design, and human-computer interfaces. Based on the AHFE 2018 International Conference on Ergonomics in Design, held on July 21-25, 2018, in Orlando, Florida, USA, the book offers a timely guide for both researchers and design practitioners, including industrial designers, human-computer interaction and user experience researchers, production engineers and applied psychologists.